A theoretical approach to accelerating innovation in manufacturing - Aristidis Mamasioulas; George Chryssolouris (Production and Manufacturing Research: An Open Access Journal)
This paper addresses the necessity of innovation acceleration, particularly in the manufacturing sector. The importance of innovation acceleration is established by a review of the innovation process literature. The paper proposes a theoretical model for the correlation of various characteristic parameters of an innovation project, with its acceleration from a quantitative point of view as well. The modelling approach stems from an analogy of mechanical systems. It attempts to assist organizations or companies in making decisions on accelerating their innovation process. The proposed innovation acceleration model is also discussed as a practical early decision tool for the innovation practitioner/manager. Limitations of the proposed model are also discussed and analysed.